Contacts and Conflicts Between Foreman and Steward - Barrett, F.D. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1955)
SummaryContacts occuring between foremen and stewards are contractual, if they arise from grievances related to the interpretation of a contract, and non-contractual, if they have to do with other matters. Potential difficulties stemming from such contacts may vary from one industry to another, from one business concern to another and from one department to another. What are, however, the attitudes toward each other which those two groups — representing management and the union respectively — will have to adopt to solve such problems ? This article is a tentative solution to the important problem of the sharing of authority in the enterprise.